Estimation of Some Genetic Parameters, Correlation and Heritability in Various Maize Traits - Hussain, Mohamed A.; Mohamad, Mohamed O. (Science Journal of University of Zakho, 2017)
The study was carried out using ten maize hybrids in spring 2015 and 2016 were planted at the field of Agriculture College, University of Duhok. All treatments arranged in Randomized Complete Block Design (RCBD) with three replications to determine the heritability, genetic advance, correlation and genetic parameters govering the inheritance of grain yield and related agronomic traits. The result showed significant difference among hybrids for studied traits in spring 2015 and 2016 and also the results revealed that hybrids and seasons interaction had a significant difference for all traits. The season’s spring 2015 was superior than spring 2016 in leaf area, days to 75% tasseling and silking, yield and its components. The hybrid (OH40 xIK8) was superior in No. of rows ear-1, No. of kernels row-1,300 kernel weight and kernel yield plant1. All studied traits recorded higher value of heritability, high genetic advance coupled with heritability was observed in leaf area and kernel yield plant-1, thus selection based on these traits will be effective in maize breeding program. Grain yield was positively correlated with leaf area and 300 kernel weight, also No. of row ear-1 exhibited positive correlation coefficient with leaf area, 300-kernell weight and kernel yield plant-1.
Keywords: Genetic Parameters; Heritability; Maize Traits; Correlation